Association of insulin-like growth factor II mrna-binding protein 3 (IMP3) expression with prognostic and morphological factors in endometrial cancer - Salum, Silas Otero Reis [UNESP]; Candido, Eduardo Batista; Domingues, Maria Aparecida Custódio [UNESP]; Ojopi, Elida Paula Benquique; Tonon, Ângela Favorito Santarem [UNESP]; da Silva-Filho, Agnaldo Lopes [UNESP] (Federação das Associações de Ginecologia e Obstetrícia, 2024)
Objective: Endometrial cancer (EC) is a heterogeneous disease with recurrence rates ranging from 15 to 20%. The discrimination of cases with a worse prognosis aims, in part, to reduce the length of surgical staging in cases with a better prognosis. This study aimed to evaluate the association between Insulin-like growth factor II mRNA-binding protein 3 (IMP3) expression and prognostic and morphological factors in EC. Methods: This retrospective, cross-sectional, analytical study included 79 EC patients-70 endometrioid carcinoma (EEC) and 9 serous carcinoma (SC)-and 74 benign endometrium controls. IMP3 expression was evaluated by immunohistochemistry-based TMA (Tissue Microarray), and the results were associated with morphological and prognostic factors, including claudins 3 and 4, estrogen and progesterone receptors, TP53, and KI67. Results: IMP3 expression was significantly higher in SC compared to EEC in both extent (p<0.001) and intensity (p=0.044). It was also significantly associated with worse prognostic factors, including degree of differentiation (p=0.024, p<0.001), staging (p<0.001; p<0.001) and metastasis (p=0.002; p<0.001). IMP3 expression was also significant in extent (p=0.002) in endometrial tumors compared with controls. In addition, protein TP53 and KI67 showed significant associations in extent and intensity, respectively. Conclusion: IMP3 expression was associated with worse prognostic factors studied. These findings suggest that IMP3 may be a potential biomarker for EC poorer prognosis.
Keywords: Endometrial neoplasms; Immunohistochemistry; IMP3; Insulin-like growth factor II; Prognosis